Analisis Pengaruh Pembebanan Terhadap Kekuatan Dielektrik Minyak Isolasi Transformator 6,6 kV/380 V Di PT.INTIBENUA PERKASATAMA Dumai - Saprianto, Saprianto; Firdaus, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The increment of electric energy comsumption causes the transformer to experience a high load and needs to be detected and treated to increase reability and reduce failure. Dielectric strength is one of detection parameter used. The purpose of this research is to analyze dielectric strength of Shell Diala S4 ZX-1 insulating oil based on changes of transformer loading. In this research, breakdown voltage is tested to see the effect of temperature rise due to changes in transformer loadon transformer oil dielectric strength. The relationship between dielectric strength, temperature rise and transformer loading is analyze using correlation and linier regression analyze. The research result strong and positive correlation (r = +0,99) between temperature rise and transformer loading, strong and negative correlation between temperature rise and dielectric strength (r = -0,98), and strong and negative correlation (r = -0,94) between transformer loading and dielectric strength.Keywords : Dielectric strength, transformer loading, liquid insulator